The Effect of Lecturers Teaching Performance on Students Satisfaction in a University - Fajriani Azis; Muhammad Azis; M. Yusuf A. Ngampo; Abd Rijal (Jurnal Office, 2021)
Student learning satisfaction is one of the indicators of teachers or lecturers success in teaching performance. It is assumed that the greater student satisfaction with a lecturer’s teaching style equates to better teaching performance by the lecturer. Current research  has established that students satisfaction level within a university learning environment correlates with the lecturers teaching performance. The present study took place within a university examining students and lecturers in the Faculty of Economics at Makassar State University  in  Indonesia.  The  sample  comprised  81  individuals  who  were investigated using a correlational descriptive study model. Data were gathered through questionnaires and the study of documents and then further analysed using a regression model  that  consisted  of  R2,  F,  t,  and  determination  tests.  Findings  were  that  a lecturer’s performance, which involves preparation, opening, core, and closing activities in a lesson, positively and significantly correlated with student satisfaction levels.